(untitled) (Research, Society and Development, 2022)
Citrus sudden death (CSD) is a biotic disease of unknown origin, transmitted by aerial vectors and buds that affects sweet oranges and tangerines cultivars budded on Rangpur lime, and Volkamer and Rough lemons rootstocks. The same cultivars onto Cleopatra and Sunki mandarins, trifoliate orange and Swingle citrumelo are asymptomatic. The objective of this study was to evaluate nine selections of citrumelo regarding tolerance to CSD and their effects on growth and production of Valencia sweet orange trees cultivated without irrigation. A completely randomized design with nine treatments (citrumelos) and five replicates, each plot represented by one tree. After 16 years in the field, no tree showed symptoms of CSD or bud union ring between the scion and the rootstock. After 14 yields, the trees onto Swingle, W-2, F80-7 and F80-8 yielded the highest productions and W-2 and F80-7 induced yearly production and did not show alternate bearing. The W-2, Swingle and F80-7 citrumelos induced the largest trees and the F80-5, F80-3 and F81-18 the smaller trees. Although they do not induce high fruit production per tree, they have the highest production efficiencies, and F80-5 motivated early production and a smaller canopy diameter, enabling greater planting density.